PENGARUH PREHEAT DAN POST WELDING HEAT TREATMENT TERHADAP SIFAT MEKANIK SAMBUNGAN LAS SMAW PADA BAJA AMUTIT K-460 - Hestiawan, Henri; Surono, Ahmad Fauzan (Jurnal MEKANIKAL, 2014)
Abstract: The Effect of Preheat and Post Weld Heat Treatment on Mechanical Properties of SMAW Welding Steel Amutit K-460. Steel welding process causes changes in the mechanical properties such as the existence of residual stress and weld cracking. This can be avoided by giving preheat and post weld heat treatment (PWHT). This research aims to determine the effects preheat and PWHT treatment on mechanical properties of SMAW welded joints in amutit steel of K-460.The specimens used were plate of amutit steel of K-460 with dimentions of 200x20x10 mm. The preheat treatment was done with a tempering process at temperatures of 260 and 370 °C with a holding time is 30 minutes. PWHT treatment was done by tempering process at temperatures of 550 and 650 °C with a holding time is 30 minutes. The welding used electrodes wrapped, shielded metal arc welding (SMAW). Tensile test results showed that preheat + PWHT treatment, and PWHT treatment can increase the value of tensile stress and strain, the tensile stress and strain values ​​were highest in specimens treated 650°C PWHT, that is amounted to σ = 567.7 MPa and ε = 3.75% . Hardness test results showed that the treatment preheat and PWHT can increase the hardness value with the highest hardness values ​​of specimens PWHT treated at 650°C, that is in the HAZ of 43.3 HRC. From these results it can be concluded that the PWHT treatment give better results in improving the mechanical properties of SMAW welded joints in amutit steel of K-460.  Keywords : Amutit steel of K-460, las SMAW